2020
DOI: 10.3390/atmos11020209
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Satellite-Derived Aerosol Optical Depth PM2.5 Bayesian Concentration Surfaces to Respiratory-Cardiovascular Chronic Disease Hospitalizations in Baltimore, Maryland

Abstract: The fine particulate matter baseline (PMB), which includes PM 2.5 monitor readings fused with Community Multiscale Air Quality (CMAQ) model predictions, using the Hierarchical Bayesian Model (HBM), is less accurate in rural areas without monitors. To address this issue, an upgraded HBM was used to form four experimental aerosol optical depth (AOD)-PM 2.5 concentration surfaces. A case-crossover design and conditional logistic regression evaluated the contribution of the AOD-PM 2.5 surfaces and PMB to four resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
66
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(71 citation statements)
references
References 74 publications
(186 reference statements)
2
66
1
Order By: Relevance
“…In addition, the ISORROPIA-II thermodynamic equilibrium model was used to study the partitioning of the WSI species in PM 2.5 aerosols. The predicted results correlated well with the observed data of the PPWD-PILS-IC system for SO 4 2− (slope = 1.0 and R 2 = 0.99) and NH 3 (slope = 1.02 and R 2 Figure S1: The size distribution of the water-soluble inorganic ions (NH 4 + , Na + , Ca 2 + , Mg 2 + , NO 3 2− , SO 4 2− and Cl − ) sampled by NCTU micro-orifice cascade impactor (NMCI) at National Chiao Tung University (NCTU) site from July 2016 to January 2018., Figure S2: Comparison of the prediction and the observation for HCl, Figure S3: Correlation of NO 3…”
supporting
confidence: 83%
See 1 more Smart Citation
“…In addition, the ISORROPIA-II thermodynamic equilibrium model was used to study the partitioning of the WSI species in PM 2.5 aerosols. The predicted results correlated well with the observed data of the PPWD-PILS-IC system for SO 4 2− (slope = 1.0 and R 2 = 0.99) and NH 3 (slope = 1.02 and R 2 Figure S1: The size distribution of the water-soluble inorganic ions (NH 4 + , Na + , Ca 2 + , Mg 2 + , NO 3 2− , SO 4 2− and Cl − ) sampled by NCTU micro-orifice cascade impactor (NMCI) at National Chiao Tung University (NCTU) site from July 2016 to January 2018., Figure S2: Comparison of the prediction and the observation for HCl, Figure S3: Correlation of NO 3…”
supporting
confidence: 83%
“…Particles smaller than 2.5 µm in diameter (PM 2.5 ) exposure has been confirmed to be associated with total mortality, cardiovascular and respiratory mortalities, lung cancer, influenza, etc. [1] due to its chronic adverse human health effects [2]. Some previous studies [3,4] have revealed that PM 2.5 constituents such as sulfate, nitrate, and ammonium were responsible for these effects.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent, accurate, and timely measurements of ambient PM2.5 concentration levels, obtained from on-the-ground air monitors, are essential for protecting human health and decreasing respiratory-cardiovascular morbidity and mortality [8,17,19,21,28,29,[35][36][37][38][39][40][41][42]. There are challenges in using ambient PM2.5 air monitors, especially those maintained by the U.S. Environmental Protection Agency (EPA) Air Quality System (AQS) [38] in epidemiologic studies [3,32]. The majority of these PM2.5 filter-based monitors measure PM2.5 concentration levels every three or six days in urban areas with higher population density [3,32,38].…”
Section: Introductionmentioning
confidence: 99%
“…There are challenges in using ambient PM2.5 air monitors, especially those maintained by the U.S. Environmental Protection Agency (EPA) Air Quality System (AQS) [38] in epidemiologic studies [3,32]. The majority of these PM2.5 filter-based monitors measure PM2.5 concentration levels every three or six days in urban areas with higher population density [3,32,38]. Few studies have evaluated differences between urban-rural areas [16,[43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation